On the inequivalence of renormalization and self-adjoint extensions for quantum singular interactions - Camblong, Horacio E. (2007)
A unified S-matrix framework of quantum singular interactions is presented for the comparison of self-adjoint extensions and physical renormalization. For the long-range conformal interaction the two methods are not equivalent, with renormalization acting as selector of a preferred extension and regulator of the unbounded Hamiltonian.